(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to develop interactive learning media based on Blooket in Informatics subjects, especially data analysis material for class VIII SMP Negeri 1 Cigandamekar. The method used is Research and Development (R&D) with the ADDIE model which includes five stages: analysis, design, development, implementation, and evaluation. Research data were collected through validation questionnaires from material experts, media experts, and student responses at the trial stage, while qualitative data were obtained through observations and field notes. Data analysis was conducted using quantitative and qualitative descriptive analysis techniques. The validation showed that the material expert gave a feasibility percentage of 90% and the media expert of 92%, both categorized as “very feasible”. Student trials were conducted in two stages, namely small group tests (6 students) with a percentage of 85% and large group tests (20 students) with a percentage of 82%, both of which were categorized as “very good”. These results show that Blooket learning media is effective in increasing students’ interest and motivation to learn. Blooket is able to create a more interactive and competitive learning atmosphere. Recommendations are addressed to teachers to utilize Blooket in learning and to further researchers to develop this media at other levels and subjects to obtain broader and deeper results.